Dendritic-Targeting GABA Neurons in Monkey Prefrontal Cortex: Comparison of Somatostatin- and Calretinin-Immunoreactive Axon Terminals - Melchitzky, Darlene S. (Synapse, 2008)
Different subclasses of γ-aminobutyric acid (GABA) cortical neurons can be distinguished by their content of neuropeptides such as somatostatin (SST), or calcium-binding proteins such as calretinin (CR). SST, but not CR, neurons have been reported to be altered in the prefrontal cortex (PFC) of subjects with schizophrenia. Understanding the functional significance of the SST neuron disturbances in schizophrenia requires knowledge of the specialized synaptic circuitry of these neurons relative to that of CR neurons. Consequently, we used immuno-electron microscopy to examine the synaptic type and postsynaptic targets of SST-immunoreactive (IR) axon terminals in monkey PFC and compared these findings with similar data for CR-IR axon terminals. SST-IR axon terminals formed exclusively symmetric synapses and contacted only dendritic shafts (86%) and dendritic spines (14%), whereas CR-IR terminals also formed synapses with cell bodies. The postsynaptic targets of SST-IR axon terminals also differed across layers with synapses onto dendritic spines more frequent in the superficial (20%) than in the deep (8%) layers. Dual-label immunoelectron microscopy revealed that CR-IR axon terminals targeted GABA-IR dendritic shafts with a greater frequency (60%) than did SST-IR axon terminals (21.5%). Conversely, SST-IR axon terminals contacted unlabeled dendritic shafts, presumably belonging to pyramidal neurons, more frequently than did CR-IR axon terminals (57% vs. 19%, respectively). This specialized synaptic circuitry of SST neurons in the primate PFC suggests that the alterations of these neurons in schizophrenia is likely to have distinct functional consequences.